2015
DOI: 10.1590/2237-6089-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence study of compulsive buying in a sample with low individual monthly income

Abstract: Introduction: Compulsive buying can be characterized as an almost irresistible impulse to acquire various items. This is a current issue and the prevalence rate in the global population is around 5 to 8%. Some surveys indicate that the problem is growing in young and low-income populations. Objectives: To evaluate the prevalence of compulsive buying among people with low personal monthly incomes and analyze relationships with socio-demographic data. Methods: The Compulsive Buying Scale was administered to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, other psychopathological disorders have not been explored; first of all, depression is a dimension very often associated with pathological purchases that might affect differently men and women as a risk factor for compulsive buying (74). Moreover, comorbidity with other behavioral addictions should be investigated (75).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other psychopathological disorders have not been explored; first of all, depression is a dimension very often associated with pathological purchases that might affect differently men and women as a risk factor for compulsive buying (74). Moreover, comorbidity with other behavioral addictions should be investigated (75).…”
Section: Discussionmentioning
confidence: 99%
“…Ergin (2010) also explained the same findings in Turkish society. However, several research findings such as (O'Guinn and Faber, 1989; Scherhorn et al , 1990; Mueller et al , 2011; Unger, et al , 2014; Leite and Silva, 2015) showed that income does not have a significant relationship to purchasing behavior compulsive. The inconsistency of the research findings indeed becomes an important issue, because humans as compulsive buying decision-makers apparently are motivated by psychological factors, as in the findings of Kellet and Bolton (2009) and Claes et al (2010), which showed that compulsive buying has negative reinforcing properties and is used to escape negative feelings such as anxiety, depression, tension, or boredom.…”
Section: Introductionmentioning
confidence: 98%